2009
DOI: 10.1016/j.jvs.2009.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and midterm outcomes of percutaneous transhepatic balloon angioplasty for symptomatic Budd-Chiari syndrome secondary to hepatic venous obstruction

Abstract: PTBA of the hepatic vein is a safe and effective treatment of BCS. It is currently the most physiologic procedure, and the risk of postoperative encephalopathy is minimized because portal flow is not diverted. Midterm outcomes are satisfactory. Further investigation of the long-term outcomes is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 18 publications
0
24
0
2
Order By: Relevance
“…Recanalization of the HV has been increasingly used in the treatment of BCS in recent years, with the purpose of relieving hepatic congestion and resolving the symptoms of BCS (1,2,8,9). A retrospective study of HV recanalization in 101 BCS patients demonstrated that clinical improvement was achieved in all patients (92/92) who successfully underwent the procedure (2).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recanalization of the HV has been increasingly used in the treatment of BCS in recent years, with the purpose of relieving hepatic congestion and resolving the symptoms of BCS (1,2,8,9). A retrospective study of HV recanalization in 101 BCS patients demonstrated that clinical improvement was achieved in all patients (92/92) who successfully underwent the procedure (2).…”
Section: Discussionmentioning
confidence: 99%
“…However, the study also demonstrated that nine patients experienced technical failure due to long-segment obstruction or diffused stenosis of the HV (2). The difficulty and challenge of HV recanalization in patients with long-segment obstruction of the HV may be attributed to the following factors: first, it is extremely difficult to cut through the long-segment of obstruction (1,2). Second, long-segment obstruction of the HV occasionally results in narrowing of the HV stem, which will impede its drainage function (2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations